Addressing weight bias and discrimination: moving beyond raising awareness to creating change. (9th October 2017) - Ramos Salas, X.; Alberga, A. S.; Cameron, E.; Estey, L.; Forhan, M.; Kirk, S. F. L.; Russell‐Mayhew, S.; Sharma, A. M.
Summary: Weight discrimination is the unjust treatment of individuals because of their weight. There have been very few interventions to address weight discrimination, due in part to the lack of consensus on key messages and strategies. The objective of the third Canadian Weight Bias Summit was to review current evidence and move towards consensus on key weight bias and obesity discrimination reduction messages and strategies. Using a modified brokered dialogue approach, participants, including researchers, health professionals, policy makers and people living with obesity, reviewed the evidence and moved towards consensus on key messages and strategies for future interventions. Participants agreed to these key messages: (1) Weight bias and obesity discrimination should not be tolerated in education, health care and public policy sectors; (2) obesity should be recognized and treated as a chronic disease in health care and policy sectors; and (3) in the education sector, weight and health need to be decoupled. Consensus on future strategies included (1) creating resources to support policy makers, (2) using personal narratives from people living with obesity to engage audiences and communicate anti‐discrimination messages and (3) developing a better clinical definition for obesity. Messages and strategies should be implemented and evaluated using consistent theoretical frameworks and methodologies.